2002
DOI: 10.1093/jat/26.3.176
|View full text |Cite
|
Sign up to set email alerts
|

Method for the Determination of Dialkyl Phosphates in Urine by Strong Anion Exchange Disk Extraction and In-Vial Derivatization

Abstract: A method for the determination of four dialkylphosphate metabolites in urine by strong anion exchange disk (SAX) was investigated. Calcium hydroxide was added to a 1-mL urine sample to reduce interference. The aliquot was passed through the SAX disk to accumulate dialkylphosphate metabolites on the disk. The retained dialkylphosphate metabolites were derivatized with methyl iodide in acetonitrile online, and the resulting methyl esters of dialkylphosphate metabolites were directly analyzed by capillary column … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 6 publications
0
10
0
2
Order By: Relevance
“…Previously, urinary DAPs have been extracted by various methods: liquid-liquid extraction [8,20,21], solid-phase extraction [14,15,22,23], and lyophilization [24]. Weerasekera et al [3] suggested that solid-phase extraction (ChemElute cartridge) and analysis using the GC-MS is the most cost-effective and rapid method.…”
Section: Advantages Of This Methodsmentioning
confidence: 99%
“…Previously, urinary DAPs have been extracted by various methods: liquid-liquid extraction [8,20,21], solid-phase extraction [14,15,22,23], and lyophilization [24]. Weerasekera et al [3] suggested that solid-phase extraction (ChemElute cartridge) and analysis using the GC-MS is the most cost-effective and rapid method.…”
Section: Advantages Of This Methodsmentioning
confidence: 99%
“…Gas chromatography (GC) has previously been the method of choice for measuring DETP and DEP in urine employing mostly either mass sensitive [12][13][14][15][16] or flame photometric [17][18][19][20][21][22] detection. However, prior to GC analysis DETP as well as DEP need to be derivatised to volatile esters.…”
Section: Chlorpyrifos Oo-diethyl-o-mentioning
confidence: 99%
“…Previously reported methods for the extraction of DAPs were liquid phase extraction [15,17], column clean-up [14,18], lyophilization [10], and azeotropic distillation [11,19]. Unfor- tunately, urinary DAP extraction using the lyophilization or azeotropic distillation technique is extremely time consuming (over 16-24 h) and is labor intensive [10].…”
Section: Introductionmentioning
confidence: 99%